Oceanography from space - United States. National Aeronautics and Space Administration. ([Pasadena, Calif.?] : The Administration, 1984)
Text on verso of plates. Antarctic sea ice -- Arctic ice floes -- Arctic sea ice --California El Nino -- Global marine winds -- Global surface temperatures --Phytoplankton & temperature patterns -- Satellites for oceanography -- Sea surface topography -- Tuna catch & ocean color -- Upper Chesapeake Bay. Mode of access: Internet.